2019
DOI: 10.3847/1538-4357/ab3407
|View full text |Cite
|
Sign up to set email alerts
|

The Far-infrared Polarization Spectrum of ρ Ophiuchi A from HAWC+/SOFIA Observations

Abstract: We report on polarimetric maps made with HAWC+/SOFIA toward ρ Oph A, the densest portion of the ρ Ophiuchi molecular complex. We employed HAWC+ bands C (89 µm) and D (154 µm). The slope of the polarization spectrum was investigated by defining the quantity R DC = p D /p C , where p C and p D represent polarization degrees in bands C and D, respectively. We find a clear correlation between R DC and the molecular hydrogen column density across the cloud. A positive slope (R DC > 1) dominates the lower density an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 96 publications
(124 reference statements)
6
40
0
Order By: Relevance
“…To achieve a thorough understanding of the filament formation process, we should aim at making direct observations of the B-field in the ISM with column densities down to 10 21 cm −2 at high spatial resolution. HAWC+ on board SOFIA pioneers polarimetry of low column density gas around bright star-forming regions (e.g., Chuss et al 2019;Santos et al 2019). Extensive observations can be conducted by future space-borne facilities (e.g., André et al 2019;Leisawitz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a thorough understanding of the filament formation process, we should aim at making direct observations of the B-field in the ISM with column densities down to 10 21 cm −2 at high spatial resolution. HAWC+ on board SOFIA pioneers polarimetry of low column density gas around bright star-forming regions (e.g., Chuss et al 2019;Santos et al 2019). Extensive observations can be conducted by future space-borne facilities (e.g., André et al 2019;Leisawitz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Observations have reported an anticorrelation trend of the fractional polarization of thermal dust emission with the column density of the gas in molecular clouds (e.g., Arce et al 1998;Whittet et al 2008;Planck Collaboration et al 2015, 2020Fissel et al 2016;Santos et al 2017Santos et al , 2019Chuss et al 2019). This trend is explained by the loss of grain alignment toward dense cores (Whittet et al 2008;Hoang et al 2020) or by the turbulent structure of magnetic field within the scale of the beam size (see Jones & Whittet 2015;Planck Collaboration et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…For example, Planck Collaboration et al (2020) showed that the 40′ spatial resolution polarization degree at 850 μm, measured by the Planck satellite toward five molecular regions, including Aquila Rift, Cham-Musca, Orion, and Ophiuchus in the Gould belt cloud, decreases for T d >19 K (see their Figure 18). Additionally, far-infrared polarimetric data observed by the High-resolution Airborne Wide band Camera Plus (HAWC+) instrument (Harper et al 2018) on board the Stratosphere Observatory for Infrared Astronomy (SOFIA) toward the molecular cloud Ophiuchus A (Santos et al 2019) at 89 μm (7 8 spatial resolution) and 154 μm (13 6 spatial resolution) also reported the decrease of the polarization degree for T d >25-32 K (see Section 2 below). These observational features are challenging the popular RAT alignment theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it possible to observe the orientation of interstellar magnetic fields through polarimetry, as was, e.g., done by Planck (Planck Collaboration et al 2018) for the Milky Way. More recently, ALMA (Cortes et al 2016), the POL-2/SCUBA2 polarimeter on the JCMT (Pattle et al 2017), and the HAWC+ polarimeter on the SOFIA telescope (Santos et al 2019;Lopez-Rodriguez et al 2020) have started opening up a new level of magnetic field surveys by producing polarization maps for star-forming molecular clouds and external galaxies. Other polarimeters are being commissioned, e.g., the TolTEC instrument on the Large Millimeter Telescope (Bryan et al 2018), or are being proposed, e.g., the B-BOP polarimeter aboard the ESA/JAXA mission SPICA (Roelfsema et al 2018;André et al 2019).…”
Section: Introductionmentioning
confidence: 99%